Quantitative estimates of time-averaging in terebratulidbrachiopod shell accumulations from a modern tropical shelf - Carroll, M.; Kowalewski, M.; Simoes, M. G.; Goodfriend, G. A. (Paleobiology, 2003)
Quantitative estimates of time-averaging in marine shellaccumulations available to date are limited primarily toaragonitic mollusk shells. We assessed time-averaging in Holoceneassemblages of calcitic brachiopod shells by direct dating ofindividual specimens of the terebratulid brachiopod Bouchardiarosea. The data were collected from exceptional (brachiopod-rich)shell assemblages, occurring surficially on a tropical mixedcarbonate-siliciclastic shelf (the Southeast Brazilian Bight, SWAtlantic), a setting that provides a good climatic andenvironmental analog for many Paleozoic brachiopod shell beds ofNorth America and Europe. A total of 82 individual brachiopodshells, collected from four shallow (5-25 m) nearshore (
id: 2231; Source type: scholarlyjournals; Object type: Article; Object type: Feature; CSAUnique: BONE5712965; AccNum: 5712965; DOI: 10.1043/0094-8373(2003)029(0381:QEOTIT)2.0.CO;2; ISSN: 0094-8373; Peer Reviewed: true